Baby Boomers\' Buying Behaviour of Consumer Products in Klang Valley - Sheau Zing, Jessica Ho (2010)
This research assesses the current state of the seniors\' buying behaviors in the two federal territories - Cyberjaya and Kuala Lumpur in Malaysia. This research focuses mainly on the boomers buying behaviors and their characteristics.